Evaluation of self-organizing communication mechanisms within a communication platform for disaster management - Schau, Volkmar; Erfurth, Christian; Rossak, Wilhelm (Electronic Communications of the EASST, 2013)
The request for IT support in rescue missions is getting stronger. In complex situations like Mass Casualty Incidents it is hard to get a good situation report which is essential for proper decisions. The requirements on IT are manifold and the development of reliable systems with networked devices is difficult and long. Additionally the evaluation of a system or its components cannot be limited on tests in some training. This paper describes an evaluation of the communication layer within a prototypical rescue management system developed by the SpeedUp project. The evaluation is done with the help of a simulation where professional and technical aspects are taken into account. Different classical routing mechanisms are compared with an approach using mobile software agents.